Доказать тождества Тригонометрия


Доказать тождества Тригонометрия

  • c) 4 * sin(a) * sin(2a) * sin(3a) = sin(2a) + sin(4a) — sin(6a) sin(2a) + sin(4a)=2sin(3a)cos(a) sin(6a)=2sin(3a)cos(3a) => sin(2a) + sin(4a) — sin(6a)=2sin(3a)cos(a)-2sin(3a)cos(3a)=2sin(3a){cos(a)-cos(3a)} теперь: cos(a)-cos(3a)=2sin(2a)sina=> 2sin(3a){cos(a)-cos(3a)}=4sin(a)sin(2a)sin(3a) что и требывалось доказать.. . d) 2 * sin(a) * sin(b) * cos(a+b) = sin^2(a+b) — sin^2(a) — sin^2(b) sin^2(a+b)=(sin(a)cos(b)+sin(b)cos(a))^2= =sin^2(a)cos^2(b)+sin^2(b)cos^2(a)+2sin(b)cos(a)sin(a)cos(b)=> sin^2(a+b) — sin^2(a) — sin^2(b)= =sin^2(a)cos^2(b)+sin^2(b)cos^2(a)+2sin(b)cos(a)sin(a)cos(b) — sin^2(a) — sin^2(b) теперь: sin^2(a)cos^2(b)-sin^2(a)= =sin^2(a){cos^2(b)-1} =-sin^2(a)sin^2(b) аналогично и sin^2(b)cos^2(a)- sin^2(b)=-sin^2(a)sin^2(b)=> sin^2(a+b) — sin^2(a) — sin^2(b)=2{sin(b)cos(a)sin(a)cos(b)-sin^2(a)sin^2(b)}= =2sin(a)sin(b)(cos(a)cos(b)-sin(a)sin(b))=2sin(a)sin(b)cos(a+b) что и требывалось доказать.. . f) sin(pi/3 — a) * cos(pi/6 + a) + cos(pi/3 — a) * sin(pi/6 + a) = 1 sin(pi/3 — a)=cos(90-60+a)=cos(30+a)=cos(pi/6 + a) cos(pi/3 — a)=sin(90-60+a)=sin(30+a)= sin(pi/6 + a) => sin(pi/3 — a) * cos(pi/6 + a) + cos(pi/3 — a) * sin(pi/6 + a)=cos^2(pi/6 + a)+sin^2(pi/6 + a)==1 что и требывалось доказать.. . Не забудь поощрить доброжилателя: )
  • f) sin(pi/3 — a) * cos(pi/6 + a) + cos(pi/3 — a) * sin(pi/6 + a)=sin(pi/3-a+pi/6+a)=sin(pi/2)=1



Предыдущий:

Следующий: